Realized genetic gain for yield and yield attributes in groundnut breeding at ICRISAT from an ERA trial - Behera, Partha Pratim; Deshmukh, Dnyaneshwar; Vemula, Anil Kumar; Bangaru, Kiranmayee; Bagudam, Rachana; Mathew, Anurag; Purohit, Ashutosh; Vishnumolakala, Aparna; Wankhade, Ankush P.; Kounain, Safinaaz; Guguloth, Nehru; Variath, Murali T.; et al. (Frontiers in Plant Science, 2025)
IntroductionGroundnut or peanut (Arachis hypogaea L.) is an important food and oilseed crop with a global production of >50 m t from ~34 m ha. The ICRISAT groundnut breeding program, established in 1976, has significantly contributed to varietal development, resulting in the release of >240 varieties in 39 countries. Estimating realized genetic gain (RGG) in a breeding program helps to measure the progress made for agronomic traits and identify gaps to guide the breeding strategy. Materials and methodsThis study was conducted to estimate realized genetic gain using an Elite Replicated Agronomic (ERA) trial, with five ERA trials representing three product concepts across market types and maturity durations. These trials included improved germplasm developed over a span of 15–20 years at ICRISAT and were evaluated for three key traits: pod yield (PY), 100 seed weight (HSW), and shelling outturn (SP). Results and discussionAmong these, PY and HSW exhibited high repeatability and genetic advance as the percentage of mean, whereas SP showed lower values. Realized genetic gain varied from 8.37 kg ha-¹ year−1 (0.48%) to 54.85 kg ha-¹ year−1 (3.91%) for PY. The Spanish Bunch germplasm recorded a higher realized GG of 46.45 kg ha-¹ year−1 (2.95%) for pod yield, compared to the Virginia Bunch germplasm with a marginal gain of 5.97 kg ha-¹ year−1 (0.23%). Higher RGG is realized in medium-duration and late-maturing germplasm with 27.1 kg ha-¹ year−1 (1.62%) and 25.32 kg ha-¹ year−1 (1.52%), respectively, while realized GG in early-maturing germplasm was 8.37 kg ha-¹ year−1 (0.5%). Among the traits, RGG was the highest for PY across all the trials. Higher RGG for PY and HSW was observed during the rainy season as compared to the post-rainy season, while SP showed a decline. This study helps breeders to optimize selection methods and design breeding strategies to enhance realized genetic gain for SP across two market types and three maturity durations. The study suggests a need for breeding strategies to enhance the rate of RGG for PY in early-maturing germplasm.